2014
DOI: 10.1002/eji.201343921
|View full text |Cite
|
Sign up to set email alerts
|

Circulating mitochondrial DNA increases with age and is a familiar trait: Implications for “inflamm‐aging”

Abstract: Mitochondrial components, including mitochondrial DNA (mtDNA), when released extracellularly, can act as "damage-associated molecular pattern" (DAMP) agents and cause inflammation. As many elderly people are characterized by a low-grade, chronic inflammatory status defined "inflamm-aging," we evaluated if circulating mtDNA can contribute to this phenomenon. Eight hundred and thirty-one Caucasian subjects were enrolled in the study, including 429 siblings aged 90-104 (90+ siblings). mtDNA plasma levels increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
247
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 326 publications
(272 citation statements)
references
References 43 publications
9
247
4
Order By: Relevance
“…42 Circulating mt-DNA levels increase with age and are positively correlated with the plasma levels of proinflammatory cytokines, such as tumor necrosis factor-α (TNFα) and IL-6 in human. 43 In addition, we previously reported that intracellular nondegraded mt-DNA induces the innate immune response leading to inflammation via TLR9-dependent signaling in mouse hearts. 44 Thus, it is possible that the increased, undigested mt-DNA associated with aging is involved in SASP development in an autonomous manner.…”
Section: Inflammaging and Senescence-associated Secretory Phenotypementioning
confidence: 99%
“…42 Circulating mt-DNA levels increase with age and are positively correlated with the plasma levels of proinflammatory cytokines, such as tumor necrosis factor-α (TNFα) and IL-6 in human. 43 In addition, we previously reported that intracellular nondegraded mt-DNA induces the innate immune response leading to inflammation via TLR9-dependent signaling in mouse hearts. 44 Thus, it is possible that the increased, undigested mt-DNA associated with aging is involved in SASP development in an autonomous manner.…”
Section: Inflammaging and Senescence-associated Secretory Phenotypementioning
confidence: 99%
“…These factors impact mitochondrial function by either promoting the accumulation of mtDNA mutations/deletions, decreased OXPHOS capacity, or excessive mtROS production, which can trigger the release of mitochondria-derived damage-associated molecular patterns (mtDAMPs), such as mtDNA fragments and some mitochondrial proteins [ 169 ]. Progressive impairment of mitochondrial function and integrity and the associated release of immunogenic molecules may thus steadily stimulate the innate immune system and promote infl ammation both systemically and within the brain [ 171 ]. Here, Fig.…”
Section: Mitochondrial Immunogenic Signalsmentioning
confidence: 99%
“…Both DNA receptors are able to sense microbial DNA during infections as well as endogenous DNA, which may be released upon cell death during aging [21]. In particular, mitochondrial DNA release from damaged mitochondria has been shown to increase with age and thus may drive inflamm-aging [22]. At this point, signaling networks for aging or infections may overlap.…”
Section: Introductionmentioning
confidence: 99%